The effect of learning interest on students' mathematical critical thinking ability in vocational high school - Anggun Apriliani; Nia Kania; Iik Nurhikmayati (Universitas Sarjanawiyata Tamansiswa, 2023)
This research investigates the impact of students' interest in learning critical mathematical thinking skills in the context of vocational high schools (SMK) by using a quantitative approach with correlational research methods. This research involved all class XI students of Ma'arif Al-Ghozali Vocational School as the population. Purposive sampling was used to select a sample of 30 students. Data analysis includes various statistical tests, including normality, linearity, correlation, and simple regression tests. The findings of this study reveal an essential relationship between students' learning interests and their mathematical critical thinking abilities. In particular, there is a significant favorable influence between interest in learning and students' critical mathematical thinking abilities. These results underscore the importance of nurturing and improving their mathematical critical thinking skills. This study contributes to our understanding of the factors influencing mathematical critical thinking skills in vocational high school students. It offers valuable insights for educators and policymakers seeking to improve mathematics education in such settings.